Fatty Acid Profiles and Nutritional Indices/Ratios of Colostrum and Transient Milk from Landrace, Large White, and Landrace × Large White Crossbred Sows - O. L. Bondoc; A. R. Ramos; A. O. Ebron (Faculty of Animal Science, Bogor Agricultural University, 2023)
Fatty acid (FA) profiles are needed to assess the nutritional quality of sow colostrum and transient milk that may be used in developing milk replacer diets for piglets and their possible use as a functional food or nutraceutical. This study analyzed the FA profiles and compared the FA-based nutritional indices/ratios of colostrum and transient milk from Landrace, Large White, and Landrace × Large White crossbred sows in a swine nucleus breeding farm in the Philippines. Colostrum and transient milk samples were collected by hand within 24 h after parturition and 36–72 h after farrowing, respectively; immediately frozen at –20 °C until analyzed for FA composition by gas chromatography. Among the major FAs with the highest proportions, palmitic acid (C16:0) and linoleic acid LA (C18:2 n-6) were higher in colostrum (20.7% and 25.0%, respectively) than in transient milk (18.7% and 18.8%, respectively). Oleic acid (C18:1 n9c) was higher in transient milk (34.9%) than in colostrum (32.2%). The polyunsaturated FA (PUFA) to saturated FA (SFA) ratio was higher in sow colostrum (0.81:1) than transient milk (0.65:1). However, transient milk had better linoleic acid to α-linolenic acid C18:3 n-3 (LA/ALA) ratio, more balanced omega-6 to omega-3 (n-6/n-3) ratio, slightly lower atherogenicity index (IA= 0.43 vs 0.46) and thrombogenicity index (IT= 0.81 vs 0.85), higher health-promoting index (HPI= 2.33 vs 2.16), and higher hypocholesterolemic/ hypercholesterolemic ratio (h/H= 2.66:1 vs 2.55:1) than colostrum. Both colostrum and transient milk from Large White sows had lower IA and IT values and higher PUFA/SFA ratio, HPI, and h/H ratio compared to Landrace sows. Crossbred sows had colostrum and transient milk with lower average IT than purebred sows. The PUFA/SFA ratio, HPI, and h/H ratio in colostrum were also higher for crossbred sows than for purebred sows. In conclusion, colostrum from crossbred sows may be used in the preparation of milk replacer formulations for piglets, while transient milk, especially from Large White sows, may be considered in the development of sow milk - based supplements in the human diet.